A better understanding of joint and survivor life expectancies in Canada - Al Fakhri, Marwa; Compton, Janice (My University, 2023)
We provide benchmark estimates for joint and survivor life expectancy for Canadian couples and show how these estimates vary with the income and employment status of couples approaching retirement. For example, a 65-year-old couple with his and her life expectancies of 15.7 and 19.8 years can expect to both be alive for only 12.5 years. 60% of these women will outlive their spouses and should expect an average of 11.9 years of widowhood; 40% of these men. will be predeceased by their wives and will live another 9.1 years on average
Keywords: Families; Households & marital status; Health; Income, pensions, spending & wealth; Population & demography; Seniors & aging